Strong anion exchange‐mediated phosphoproteomics reveals extensive human non‐canonical phosphorylation. (21st August 2019) - Hardman, Gemma; Perkins, Simon; Brownridge, Philip J; Clarke, Christopher J; Byrne, Dominic P; Campbell, Amy E; Kalyuzhnyy, Anton; Myall, Ashleigh; Eyers, Patrick A; Jones, Andrew R; Eyers, Claire E
Abstract: Phosphorylation is a key regulator of protein function under (patho)physiological conditions, and defining site‐specific phosphorylation is essential to understand basic and disease biology. In vertebrates, the investigative focus has primarily been on serine, threonine and tyrosine phosphorylation, but mounting evidence suggests that phosphorylation of other "non‐canonical" amino acids also regulates critical aspects of cell biology. However, standard methods of phosphoprotein characterisation are largely unsuitable for the analysis of non‐canonical phosphorylation due to their relative instability under acidic conditions and/or elevated temperature. Consequently, the complete landscape of phosphorylation remains unexplored. Here, we report an u nbiased p hosphopeptide enrichment strategy based on strong a nion e x change (SAX) chromatography (UPAX), which permits identification of histidine (His), arginine (Arg), lysine (Lys), aspartate (Asp), glutamate (Glu) and cysteine (Cys) phosphorylation sites on human proteins by mass spectrometry‐based phosphoproteomics. Remarkably, under basal conditions, and having accounted for false site localisation probabilities, the number of unique non‐canonical phosphosites is approximately one‐third of the number of observed canonical phosphosites. Our resource reveals the previously unappreciated diversity of protein phosphorylation in human cells, and opens up avenues for high‐throughput exploration of non‐canonical phosphorylation in all organisms. Synopsis: Phosphoproteomic analyses in vertebrates have focussed mainly on serine/threonine/tyrosine phosphorylation. A new phosphopeptide enrichment strategy now reveals the extent of non‐canonical phosphorylation in human cells, opening doors to functional investigations. Unbiased strong anion exchange (SAX)‐based phosphopeptide separation at pH 6.8 (UPAX) permits identification of histidine, aspartate, glutamate, lysine, arginine and cysteine phosphopeptides by tandem mass spectrometry. Non‐canonical (His, Asp, Glu, Lys, Arg, Cys) protein phosphorylation is extensive in human cell extracts, with the number of non‐canonical phosphosites approximately one‐third that of canonical pSer, pThr and pTyr phosphorylation. Sequence motifs for non‐canonical phosphorylation sites in human proteins are reported for the first time. Abstract : A new phosphopeptide enrichment strategy vastly expands the human phospho proteome beyond Ser/Thr/Tyr phosphorylation.